Coral cavity sponges depend on reef-derived food resources: stable isotope and fatty acid constraints - van Duyl, Fleur C. (Springer Berlin Heidelberg, 2011)
The diet of cavity sponges on the narrow fringing reefs of Curaçao, Caribbean was studied. The origin and resources of the bulk food of these sponges, i.e., dissolved organic matter (DOM), were identified using stable carbon and nitrogen isotopes and fatty acid biomarkers. We found that phytoplankton and its derived DOM from the adjacent open sea and from reef overlying water is not the main source of food for most of the sponges examined nor is bacterioplankton. Interestingly, dual stable isotope signatures (δ(13)C(org), δ(15)N(org)) and fatty acid biomarkers appoint coral mucus and organic matter derived from crustose coralline algae (CCA) as probable food sources for encrusting sponges. Mucus-derived DOM may contribute up to 66% to the diet of examined sponges based on results of dual isotope mixing model analysis. The contribution of CCA (as purported representative for benthic algae) was smaller with values up to 31%. Together, mucus- and CCA-derived substrates contributed for 48–73% to the diet of sponges. The presence of the exogenous fatty acid 20:4ω6 in sponges, which is abundant in coral mucus of Madracis mirabilis and in CCA, highlights these reef-derived resources as sources of nutrition for DOM feeding cavity sponges. The relatively high concentrations of exogenous 20:4ω6 in all sponges examined supports our hypothesis that the bulk of the food of the cavity sponge community is reef-derived. Our results imply that cavity sponges play an important role in conserving food and energy produced within the reef.